1998
DOI: 10.1038/sj.ijir.3900300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Korean red ginseng on the rabbit corpus cavernosal smooth muscle

Abstract: The extracts of Korean red ginseng (EKG) is a complex mixture containing ginsenosides, polysaccharides, and several other products. Animal experiments have shown that the intravenous administration of extract of ginseng reduces blood pressure. Recently, it has been reported that ginseng has a relaxing effect on vascular smooth muscle and that the relaxation is associated with nitric oxide (NO) released from the vascular endothelium. The present study was undertaken to investigate the effects of EKG on isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 29 publications
2
42
0
1
Order By: Relevance
“…5,20,21 In a previous study, we described several candidate pathways involved in KRG-induced relaxation. 5 One of those pathways involves NO, a potent relaxant for peripheral vascular smooth muscle, whose action is mediated by cyclic GMP. Acetylcholine may stimulate the formation of an endothelium derived relaxing factor, which has subsequently been identified as either a NO, or a chemically unstable NO precursor.…”
Section: Pro-erectile Effects Of Ginseng Berry Ks Cho Et Al 505mentioning
confidence: 99%
See 2 more Smart Citations
“…5,20,21 In a previous study, we described several candidate pathways involved in KRG-induced relaxation. 5 One of those pathways involves NO, a potent relaxant for peripheral vascular smooth muscle, whose action is mediated by cyclic GMP. Acetylcholine may stimulate the formation of an endothelium derived relaxing factor, which has subsequently been identified as either a NO, or a chemically unstable NO precursor.…”
Section: Pro-erectile Effects Of Ginseng Berry Ks Cho Et Al 505mentioning
confidence: 99%
“…2,3 Among these, various reports have promoted the root-derived Korean red gingseng (KRG; Panax ginseng) as alternative treatment for ED, citing the stimulatory effect of KRG on the corpus cavernosum smooth muscle (CCSM) of the penis. [4][5][6] The principal active ingredients of ginseng are ginsenosides (also called ginseng saponins), which are amphiphilic molecules comprised of an aglycon backbone (a hydrophobic four-ring steroid-like structure) linked to hydrophilic carbohydrate side chains that consist of monomers, dimers and tetramers. 5,7 Ginsenoside is widely and variably distributed thoughout the ginseng plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19] It has been shown that there are many Chinese traditional herbals that can enhance sexual activity. [20][21][22][23][24] Recently, there is an increasing interest in investigating their effective components.…”
Section: Introductionmentioning
confidence: 99%
“…2 To date, most studies investigating the efficacy of ginseng in the treatment of ED have been performed in animals where it has been shown to relax cavernosal smooth muscle in rabbits and decrease time to ejaculation in rats. 22,28 Recently, two clinical studies have demonstrated ginseng's effectiveness in improving parameters of erectile function such as penile rigidity and duration of erection. 29,30 Documented adverse effects of ginseng include gastrointestinal disturbances and dermatitis, and it is contraindicated in patients with acute inflammatory disease and bronchitis.…”
Section: Discussionmentioning
confidence: 99%